Managing Director's Global Policy Agenda to the International Monetary and Financial Committee. (Policy Papers; Policy Paper ;, 2013)
Over the past five years much has been done to avoid the worst and stave off a great depression. While the recovery has been disappointing until recently, there are some encouraging signs that activity is strengthening in advanced economies. Breaking the cycle of growth shortfalls and recurring market jitters requires carefully managing multiple transitions that are already underway. These transitions include the normalization of global financial conditions; a shift in global growth dynamics, and a rebalancing of global demand; and the completion of reforms to the international financial system. Much more ambitious reform implementation and policy coherence are needed to address these challenges and avoid five more years of growth disappointments.